Прогнозування енергоспоживання для сектора загального державного управління в економіці України до 2040 року - Maistrenko N.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
The article clarifies the normative method of forecasting the demand for energy resources at different hierarchical levels of economic construction by including an improved three-level method of calculating forecast levels of energy consumption taking into account regional specifics by the types of economic activity with the current division of the country’s economy. The methodic takes into account both the overall energy saving potential in the country as a whole, at the level of economic sectors, at the level of individual industries (services) and its features at the regional level (region, city, village, town, territorial community) in certain (selected) in the provision of services (production). The volumes of perspective structural (intersectional and intrasectional) and technological electric saving in Ukraine and the region of Kyiv region according to the scenarios of economic development and main consumers are analyzed. The study has been conducted according to a conservative scenario as part of the overall forecast of energy consumption in Ukraine. As a result, the forecast of electricity consumption in the economy of Ukraine for the period up to 2040 for the general government sector and others is presented. This sector is included in the Other Foreign Economic Activities sector and at the same time consists of sections: Public Administration and Defense; compulsory social insurance; Education; Health care and providing social assistance, etc. The rest part of the economy was taken into account in the industrial sector. Consumption of population in a general way is determined by the specific costs per capita in the base year and the forecast of its number for the study period at the level of the country and region. To clarify it, the technological potential of energy saving is determined. In the example of the Kyiv region, calculations of electricity consumption levels at the macro and meso levels for the region were performed.